Cost-effectiveness of cholecystectomy compared to conservative management in people presenting with uncomplicated symptomatic gallstones or cholecystitis in India. (7th February 2023) - Haridoss, Madhumitha; Kumar, Sajith; Natarajan, Meenakumari; Sasidharan, Akhil; Rajsekar, Kavitha; Oswal, Nikhil Kumar; Bagepally, Bhavani Shankara
ABSTRACT: Objectives: Gallstone diseases impose a significant economic burden on the health care system; thus, determining cost-effective management for gallstones is essential. We aim to estimate the cost-effectiveness of cholecystectomy compared with conservative management in individuals with uncomplicated symptomatic gallstones or cholecystitis in India. Methods: A decision-analytic Markov model was used to compare the costs and QALY of early laparoscopic cholecystectomy (ELC), delayed laparoscopic cholecystectomy (DLC), and conservative management (CM) in patients with symptomatic uncomplicated gallstone/cholecystitis from an Indian health system perspective. Incremental cost-effectiveness ratio (ICER) was calculated. One-way and probabilistic sensitivity analyses were performed to test parameter uncertainties. Results: ELC and DLC, compared to CM, incurred an incremental cost of -₹10, 948 (146) and ₹1, 054 (14) for the 0.032 QALYs gained. The ICER was -₹3, 42, 758 (4577) for ELC vs. CM, and ₹33, 183 (443) for DLC vs. CM, suggesting ELC and DLC are cost-effective. ELC saved ₹12, 001 (160) for 0.0002 QALYs gained compared to DLC, resulting in an ICER of -₹6, 43, 89, 441 (8, 59, 733). The results were robust to changes in the input parameters in sensitivity analyses. Conclusion: ELC is dominant compared to both DLC and CM, and DLC is more cost-effective than CM. Thus, ELC may be preferable to other gallstone disease managements.